2019
DOI: 10.1002/jcla.22866
|View full text |Cite
|
Sign up to set email alerts
|

Sample‐to‐cutoff ratios using Architect HIV Ag/Ab Combo: The influence with the results of supplemental tests and optimal cutoff value to predict HIV infection

Abstract: BackgroundThe Architect HIV Ag/Ab Combo has excellent performance for HIV screening; however, the false‐positive rate (FPR) was high in low HIV prevalence setting.ObjectivesThe purpose of this study was to analyze the influence of sample‐to‐cutoff (s/co) ratios by Architect HIV Ag/Ab Combo with the results of confirmatory test and explore the potential utility of s/co to predict HIV infection.MethodsA retrospective review on Architect HIV Ag/Ab Combo reactive results was performed at a teaching hospital in Xi'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…There were 10 kinds of WB bands patterns in all 82 WB-positive specimens ( Table 1 ). No relation between WB bands number and COI values was observed, which is different from the previous study by Wang et al [ 30 ].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…There were 10 kinds of WB bands patterns in all 82 WB-positive specimens ( Table 1 ). No relation between WB bands number and COI values was observed, which is different from the previous study by Wang et al [ 30 ].…”
Section: Resultscontrasting
confidence: 99%
“…Hence, HIV screening assay must be highly sensitive and can detect all HIV subtypes. Currently in China, few of new HIV infection can be detected at early period due to rare application of 4-th generation assay and nucleic acid (NAT) and p24 antigen tests in many hospitals [ 30 ]. In addition, 4-th generation assay with high sensitivity has a high false-positive rate (FPR = 0.14% in our study), which requires many retests and confirmatory tests subsequently according to the current diagnostic algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…All studies include a PPV for the screening test as well as a suggested S/Co ratio for optimal screening test performance. Study N = PPV Mean S/Co ratio of True Positives (Range) Mean S/Co ratio of False Positives (Range) Optimal S/Co ratio (100 % sensitivity maintained unless otherwise stated) Significance of difference in S/Co ratios Xia et al [25] 150,980 28 % 643.5 (9.95 - ≈ 1200) 3.174 (1–23.77) 9.87 (ROC) P < 0.0001 Wang et al [20] 84,702 44 % 458.15 (30.32–1171.33) 3.11 (1–18.55) 24.44 (ROC) P < 0.0001 Kim et al [10] 155,339 31.2 % overall (2.5 % for female samples) 385.97 (7.28–739.98) 2.94 (1.00–34.59) 8.8 (sensitivity 99.36 %) 6.6 (sensitivity 100 %) …”
Section: Discussionmentioning
confidence: 99%
“…There are some reports on comparative studies on S/CO ratio between true and false positive HIV test results from actual field use. Here, the authors summarize available published data on S/CO ratio [1][2][3] . From available data on 108,196 HIV screening tests, there were 20 true and 16 false positive results respectively.…”
mentioning
confidence: 99%